The Japanese conspiracy : the Oahu sugar strike of 1920 - Duus, Masayo, 1938-2022 (University of California Press, 1999)
A community of sugar cane workers from Japan strike for a wage increase in 1920 Oahu, straining relations between Japan and the United States, underscoring racial tensions between Japanese labor and the American sugar industry, and leading to the passage of the Japanese Exclusion Act of 1924.
Keywords: Strikes and lockouts -- Hawaii -- Oahu -- History.; Noncitizens -- Hawaii -- Oahu -- History.; Japanese -- Legal status, laws, etc. -- Hawaii -- Oahu -- History.; Emigration and immigration law -- United States -- History.; Oahu (Hawaii) -- Social conditions.; United States -- Foreign relations -- Japan.; Japan -- Foreign relations -- United States.; Grèves et lock-out -- Hawaii -- Oahu -- Histoire.; Oahu (Hawaii) -- Conditions sociales.; Japon -- Relations extérieures -- États-Unis.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; HISTORY / United States / State & Local / West (AK, CA, CO, HI, ID, MT, NV, UT, WY); Noncitizens; Emigration and immigration law; Diplomatic relations; Japanese -- Legal status, laws, etc.; Social conditions; Strikes and lockouts; Hawaii -- Oahu; Japan; United States; History